2016
DOI: 10.18668/ng.2016.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ nanotlenków glinu i cynku na parametry świeżego i stwardniałego zaczynu cementowego

Abstract: Wpływ nanotlenków glinu i cynku na parametry świeżego i stwardniałego zaczynu cementowego Nanomateriały i ich unikatowe właściwości znalazły już zastosowanie w wielu gałęziach przemysłu, umożliwia-jąc tworzenie materiałów o bardzo korzystnych właściwościach, pozwalając poprawić cechy produktów już istniejących oraz tworzyć nowe. Poprawa parametrów mechanicznych materiałów zawierających dodatek nanocząstek to tylko jedna z wielu możliwości ich zastosowania. W artykule przedstawiono wstępne wyniki badań wpływu n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Several studies have been reported that concrete strength improvement as a result of the addition of small-size nanosilica is much higher than that of silica fume, even though the quantity used is much smaller for the former. This phenomenon has been explained by a newly proposed strengthening mechanism of nanosilica in which it act as nucleation sites for CSH, which not only accelerates early hydration of Portland cement, but also positively modifies the microstructure of CSH for stronger and more durable cement [2]. It was found that the rate of pozzolanic reaction depends on the specific surface area available in the reaction.…”
Section: Pozzolanic Effect and Crystallization Controlmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have been reported that concrete strength improvement as a result of the addition of small-size nanosilica is much higher than that of silica fume, even though the quantity used is much smaller for the former. This phenomenon has been explained by a newly proposed strengthening mechanism of nanosilica in which it act as nucleation sites for CSH, which not only accelerates early hydration of Portland cement, but also positively modifies the microstructure of CSH for stronger and more durable cement [2]. It was found that the rate of pozzolanic reaction depends on the specific surface area available in the reaction.…”
Section: Pozzolanic Effect and Crystallization Controlmentioning
confidence: 97%
“…The properties of the final product are influenced by such process parameters as: temperature, duration of process or mixing speed. The classic method of producing silica with a spherical structure and a particle size of 0.5 nm to 200 nm is the Stöber method based on conducting a sol-gel process in an ammonia environment [2,5].…”
Section: Nanosilica As An Addition To Cement Slurriesmentioning
confidence: 99%
See 1 more Smart Citation
“…W ciągu ostatnich kilku lat wielu naukowców przeprowadziło badania związane z poprawą i zrozumieniem zachowania zaczynów cementowych z dodatkiem nanomateriałów. Przebadano kilka rodzajów nanomateriałów, takich jak nanokrzemionka, nanoił, nanotlenki żelaza, glinu, cynku i tytanu (Li H. et al, 2004;Li Z. et al, 2006;Ershadi i Ebadi, 2011;Nazari i Riahi, 2011;De La Roij et al, 2012;Dębińska, 2014Dębińska, , 2015Dębińska, , 2016Dębińska et al, 2016;Rahman et al, 2016aRahman et al, , 2016b. Włączenie materiałów nanometrycznych do struktury hydratu krzemianu wapnia (C-S-H) skutkuje mocniejszą i bardziej plastyczną matrycą cementową, która może zapobiec propagacji pęknięć w stwardniałym zaczynie cementowym (De La Roij et al, 2012).…”
Section: Wprowadzenieunclassified
“…W ciągu ostatnich kilku lat wielu naukowców przeprowadziło badania związane z poprawą i zrozumieniem zachowania zaczynów cementowych z dodatkiem nanomateriałów. Przebadano kilka rodzajów nanomateriałów, takich jak nanokrzemionka, nanoił, nanotlenki żelaza, glinu, cynku i tytanu (Rahman et al, 2016;Dębińska, 2014Dębińska, , 2015Dębińska, , 2016Rahman i Murtaza, 2015;Dębińska et al, 2016). Włączenie materiałów nanometrycznych do struktury hydratu krzemianu wapnia (C-S-H) skutkuje mocniejszą i bardziej plastyczną matrycą cementową, która może zapobiec propagacji pęknięć w stwardniałym zaczynie (Roij et al, 2012).…”
Section: Wprowadzenieunclassified